Mortality Among Hospitalized Patients With Pleural Effusions. A Multicenter, Observational, Prospective Study - Markatis, Eleftherios; Perlepe, Garifallia; Afthinos, Andreas; Pagkratis, Konstantinos; Varsamas, Charalampos; Chaini, Eleftheria; Papanikolaou, Ilias C.; Gourgoulianis, Konstantinos I. (Frontiers in Medicine, 2022)
Background: Data regarding the prognostic significance of pleural effusion (PE) are scarce. Objective: Explore the impact of PE on mortality among hospitalised patients. Methods: Multicenter prospective observational study. Patients that underwent computed tomography (thorax and/or abdomen) and in which PE was detected, were admitted to the study. PE was classified by size on CT, anatomical distribution, diagnosis, and Light's criteria. Charlson comorbidity index (CCI), APACHE II, and SOFA score were calculated. Mortality at 1 month and 1 year were recorded. Results: 508 subjects, mean age 78 years. Overall mortality was 22.6% at 1 month and 49.4% at 1 year. Bilateral effusions were associated with higher mortality than unilateral effusions at 1 month (32% versus 13.3% p=0,005) and large effusions with higher mortality than small effusions at 1 year (66.6% versus 43.3%, p<0, 01). On multivariate analysis age, CCI, APACHE II, SOFA score, and bilateral distribution were associated with short-term mortality, while long-term significant predictors were CCI, APACHE II, SOFA, and malignant etiology. Exudates (excluding MPE) exhibited a survival benefit at both 1 month and 1 year but due to the smaller sample, fluid characteristics were not included in the multivariate analysis. A separate analysis of solely MPEs identified high APACHE score and bilateral distribution as the factors associated with worse survival among MPEs. Conclusions: Pleural effusion is a marker of advanced disease. Mortality is higher within the first month in patients with PEs related to organ failure, while patients with MPE have the worst long-term outcome. Independent predictors of mortality, apart from CCI, APACHE II, and SOFA scores, are age and bilateral distribution in the short-term, and malignancy in the long-term.